THE EFFECT OF FINANCIAL EXPERTISE ON COMPENSATION AND BOARD OF DIRECTORS TURNOVER - Danar Irianto; Nuranisa Anugerah (Pusat P2M Politeknik Negeri Batam, 2018)
This research aims to explains association between financial expertise of directors to directors compensation and directors turnover of Indonesia non financial company in 2011-2012. Using ordinary least square regression we used four variables to define financial expertise of directors: age of the directors, tenure of the directors, the post-graduate degree (MBA), and the accounting certification (CPA). However, this study found no association financial expertise to compensation and directors turnover. We hope this study can contributes to financial expertise, compensation, and turnover literature. We also provide implications for companies in determining the compensation of directors based on financial expertise. Further research can be improve by add new variabel such as complexcity and board size.